The effect of pharmacy visit to the potential drug interactions in the hospitalized geriatric patient at Dahlia ward Prof. Dr. Margono Soekarjo hospital - Heny Ekowati; Tunggul Adi P.; Trisnowati .; Budi Rahardjo (Indonesian Journal of Pharmacy, 2006)
Pharmaceutical care is the responsible provision of drug therapy for the purpose of achieving definite outcomes that improve a patient’s quality of life. Ward pharmacy is one way to realizing pharmaceutical care. This research’s aim was to study potential drug interactions in geriatric patient hospitalized at Dahlia ward Prof. Dr. Margono Soekarjo hospital, before and after ward pharmacy. The research used before and after study method, comparing potential drug interactions before and after ward pharmacy from March - June 2006. The different significance of drug interactions before and after ward pharmacy tested with Mann-Whitney test. Software which used in statistical analysis was SPSS (Statistical Product Social Science for) version 11.The study showed that total potential drug interaction before and after ward pharmacy were 3,69% and 5,12%. Drug interactions with significance rating 1, 2, and 3 before ward pharmacy were 0.08 ; 0.16 and 0.04 respectively ; while after ward pharmacy were 0.33 ; 0.14 and 0.09 respectively. The statistical analysis indicate that there was no a significance difference of drug interactions before and  after ward pharmacy (P> 0,05). The result was used to improve the system of pharmaceutical care in RSUD Prof. Dr Margono Soekarjo Purwokerto.Key words: ward pharmacy, geriatric patient, potential drug interaction